2002
DOI: 10.1161/01.cir.0000037062.35762.b4
|View full text |Cite
|
Sign up to set email alerts
|

Alternans of Atrial Action Potentials During Atrial Flutter as a Precursor to Atrial Fibrillation

Abstract: Background-The mechanisms underlying the transition of typical atrial flutter (Afl) to fibrillation (AF) remain unclear.We set out to test the hypothesis that Afl disorganizes to AF via alternans of atrial action potentials. Methods and Results-In 38 patients with Afl, monophasic action potentials (MAPs) were recorded at the isthmus and either high or low right atrium (HRA, LRA) during overdrive pacing to 160 ms or to the initiation of AF, whichever came first. MAP duration measured at 90% repolarization was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 40 publications
(35 reference statements)
5
116
0
Order By: Relevance
“…8,21 Recently Narayan et al described MAP alternans associated with developing AF and reported that, in patients with typical counterclockwise AFL, rate maladaptation of APD at the isthmus during AFL led to APD alternans, which preceded the subsequent disorganization to AF. 22 The present study demonstrated that DA was induced by rapid atrial pacing, indicating that the temporal and spatial dispersion of atrial repolarization increased as the pacing rate increased.…”
Section: Atrial Spatiotemporal Dispersion and Initiation Of Afsupporting
confidence: 54%
“…8,21 Recently Narayan et al described MAP alternans associated with developing AF and reported that, in patients with typical counterclockwise AFL, rate maladaptation of APD at the isthmus during AFL led to APD alternans, which preceded the subsequent disorganization to AF. 22 The present study demonstrated that DA was induced by rapid atrial pacing, indicating that the temporal and spatial dispersion of atrial repolarization increased as the pacing rate increased.…”
Section: Atrial Spatiotemporal Dispersion and Initiation Of Afsupporting
confidence: 54%
“…The data demonstrate that beat-to-beat alternation of the time-dependent restitution properties and refractory kinetics of the SR Ca 2ϩ release mechanism represents a key mechanism underlying cardiac alternans. calcium alternans; ryanodine receptor; refractoriness; sarcoplasmic reticulum calcium release CARDIAC ALTERNANS is a recognized risk factor for cardiac arrhythmia and sudden cardiac death (58,60,61) and has been directly linked to atrial fibrillation (26,42), the most common form of cardiac arrhythmia (43). At the cellular level, cardiac alternans is defined by cyclic, beat-to-beat variations in contraction amplitude (mechanical alternans), action potential (AP) duration (APD; electrical or APD alternans), and Ca 2ϩ transient amplitude (Ca 2ϩ alternans) at constant stimulation frequency (e.g., Ref.…”
mentioning
confidence: 99%
“…The focus was placed on atrial myocytes for several reasons: 1) atrial arrhythmias (particularly atrial fibrillation) are the most common and most prevalent form of cardiac arrhythmia (e.g., Ref. 43) and have been linked directly to alternans (26,42); 2) at the cellular level, due to the lack of a t-tubular membrane system and the special features of Ca 2ϩ release during excitation-contraction coupling (27,33,39,40,53,66), atrial myocytes are particularly susceptible to pacing and metabolically induced Ca 2ϩ alternans (28,34); and 3) Ca 2ϩ alternans can be subcellularly inhomogeneous (1,2,15,24), which is again particularly pronounced in atrial tissue (28,32). We have demonstrated subcellular transverse and longitudinal gradients of the degree of Ca 2ϩ alternans and subcellular regions alternating out of phase.…”
mentioning
confidence: 99%
“…Contact electrograms of AF are analysed using algorithms that analyse activation using the rate-dynamics of human left and right atrial (RA) action potential duration [35][36][37][38] to limit the shortest cycle length at any rate and rate-dependent conduction velocity 37,39 …”
Section: Mapping Rotors and Focal Sources In Human Atrial Fibrillationmentioning
confidence: 99%